2021
DOI: 10.1002/stvr.1802
|View full text |Cite
|
Sign up to set email alerts
|

HOTFUZ: Cost‐effective higher‐order mutation‐based fault localization

Abstract: Fault localization techniques are used to deduce the exact source of a failure from a set of failure indications while debugging software and play a crucial role in improving software quality. Mutation‐based fault localization (MBFL) techniques are proposed to localize faults at a finer granularity and with higher accuracy than traditional fault localization techniques. Despite the technique's effectiveness, the immense cost of mutation analysis hinders MBFL's practical application in the industry. Various mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…HOM testing regards HOMs as representations of complex faults which can alleviate the of complex mutation testing challenge. For instance, HOMs are valuable in reducing testing costs [34][35][36][37], assessing the quality of test suites [38], facilitating test data generation [39], performing coupling effect analysis [19,40] and executing fault localization [41,42].…”
Section: Higher Order Mutants (Hom) Testingmentioning
confidence: 99%
“…HOM testing regards HOMs as representations of complex faults which can alleviate the of complex mutation testing challenge. For instance, HOMs are valuable in reducing testing costs [34][35][36][37], assessing the quality of test suites [38], facilitating test data generation [39], performing coupling effect analysis [19,40] and executing fault localization [41,42].…”
Section: Higher Order Mutants (Hom) Testingmentioning
confidence: 99%
“…MBFL techniques suffer from the cost of mutation analysis, as it requires a massive number of test executions against the generated mutants. To reduce the number of mutants needed to be inspected, Metallaxis [13] adopts mutant sampling while HOTFUZ [18] combines first-order mutants to build higher-order mutants and computes suspicious score only on them. Their results showed that this reduces the number of total mutants as well as equivalent mutants that contribute nothing to the fault localisation.…”
Section: Mutation-based Fault Localisationmentioning
confidence: 99%
“…Although the usefulness of MBFL techniques has long been demonstrated, the substantial cost of mutation analysis has hampered their practical applications. The cost reduction techniques for MBFL are in line with the cost reduction techniques for traditional mutation testing: random sampling of the mutants [13] and higher-order mutants [18]. They have reduced the number of mutants and test executions, but still they are not suitable for large systems like Google's on which more than ten million test executions take place everyday [19].…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al [41] proposed a higher-order mutation-based fault localization technique called HOTFUZ. The approach uses HOMs to reduce the cost while minimizing the accuracy degradation.…”
Section: Related Workmentioning
confidence: 99%